DABCO-modified magnetic core-shell as an efficient nanocatalyst for synthesizing polyhydroquinoline derivatives - Esfandiari, Mozhgan; Salimi Beni, Alireza (Frontiers in Chemistry, 2025)
The fabrication of core-shell structured magnetic resorcinol-formaldehyde composites has garnered considerable attention within the scientific community in recent years. A key area of focus has been the immobilization of homogeneous catalysts onto the surfaces of these materials and transforming them into heterogeneous catalysts. In this study, a novel quaternary ammonium salt catalyst was synthesized by immobilizing 1,4-diazabicyclo [2.2.2] octane (DABCO) on resorcinol-formaldehyde-modified Fe3O4 nanocomposite as a support (Fe3O4@RF/Pr-DABCO). The Fe3O4@RF/Pr-DABCO nanocomposite was characterized using various physicochemical techniques, including FT-IR, VSM, SEM, XRD, and TGA. The Fe3O4@RF/Pr-DABCO nanocomposite was employed as a power nanocatalyst in the Hantzsch reaction for synthesizing polyhydroquinoline derivatives using aromatic aldehydes, ammonium acetate, dimedone and ethyl acetoacetate. Various aromatic aldehydes were used as substrates in the presence of 0.003 g of Fe3O4@RF/Pr-DABCO under solvent-free condution at 60 °C, achieving high to excellent yields (90-99%) within short reaction times (5-15 min). Furthermore, this nanocatalyst showed excellent reusability and maintained its catalytic activity for at least eight consecutive cycles without a significant decrease in efficiency. These results demonstrate the potential of the Fe3O4@RF/Pr-DABCO nanocomposite as an efficient and sustainable catalyst for the synthesis of polyhydroquinoline derivatives via the Hantzsch reaction.